Cardiovascular Health and Near Visual Impairment Among Older Adults in the Republic of Congo: A Population-Based Study. (2nd December 2020) - Gbessemehlan, Antoine; Helmer, Catherine; Delcourt, Cécile; Boumediene, Farid; Ndamba-Bandzouzi, Bébène; Mbelesso, Pascal; Samba, Harielle; Kehoua, Gilles; Désormais, Ileana; Lacroix, Philippe; Aboyans, Victor; Dartigues, Jean-François; et al.
Abstract: Background: Visual impairment (VI) and determinants of poor cardiovascular health are very common in Sub-Saharan Africa. However, we do not know whether these determinants are associated with VI among older adults in this region. This study aimed at investigating the association between the determinants of poor cardiovascular health and near VI among older adults living in Congo. Methods: Participants were Congolese adults aged 65 or older included in Epidemiology of Dementia in Central Africa—Follow-up population-based cohort. Near VI was defined as visual acuity less than 20/40 measured at 30 cm. Associations between determinants of poor cardiovascular health collected at baseline and near visual acuity measured at first follow-up were investigated using multivariable logistic regression models. Results: Among the 549 participants included, 378 (68.8%; 95% confidence interval [CI]: 64.9%–72.7%]) had near VI. Of the determinants of poor cardiovascular health explored, we found that having high body mass index of at least 25 kg/m 2 (odds ratio [OR] = 2.15; 95% CI: 1.25–3.68), diabetes (OR = 2.12; 95% CI: 1.06–4.25) and hypertension (OR = 1.65; 95% CI: 1.02–2.64) were independently associated with near VI. Conclusions: Several determinants of poor cardiovascular health were associated with near VI in this population. This study suggests that promoting good cardiovascular health could represent a target for VI prevention among older adults.